Impact of Opioid Administration in the Intensive Care Unit and Subsequent Use in Opioid-Naïve Patients - Krancevich, Niki M; Belfer, Julie J; Draper, Heather M; Schmidt, Kyle J (The Annals of pharmacotherapy, 2022)
Opioids are a mainstay of therapy for patients in the intensive care unit (ICU) as part of the analgesia-first approach to sedation. Despite knowledge of acute consequences of opioid based analgosedation, less is known about the potential long-term consequences, including the effect of opioid administration in the ICU on subsequent opioid use in opioid-naïve patients. To evaluate the relationship between ICU opioid administration to opioid-naïve patients and subsequent opioid use following discharge. A query of the electronic medical record was performed to identify opioid-naïve adult patients admitted directly to an ICU. Patients who received continuous intravenous infusion of fentanyl, hydromorphone, or morphine were screened for inclusion into the analysis. Of the 342 patients included for analysis, 164 (47.1%) received an opioid at hospital discharge. In total, 17 of the 342 patients (5.0%) became long-term users, noted to be more common in patients who received an opioid prescription at discharge (8.7% vs 1.6%; = 0.006). Neither total ICU morphine milligram equivalent (MME) nor average daily ICU MME administration were found to correlate with daily MME prescription quantity at discharge ( = 0.008 and = 0.03, respectively). Following control for potentially confounding variables, total ICU MME administration remained an insignificant predictor of subsequent receipt of an opioid prescription at discharge and long-term opioid use. This study failed to find a significant relationship between ICU opioid use in opioid-naïve patients and subsequent opioid use. These findings highlight the need to focus on transitions points between the ICU and discharge as potential opportunities to reduce inappropriate opioid continuation.